Strain-driven auto-detachable patterning of flexible electrodes - Lv, Zhisheng (2022)
Flexible electrodes that are multilayer, multimaterial, and conformal are pivotal for multifunctional wearable electronics. Traditional electronic circuits manufacturing requires substrate-supported transfer printing, which limits their multilayer integrity and device conformability on arbitrary surfaces. Herein, a "shrinkage-assisted patterning by evaporation" (SHAPE) method is reported, by employing evaporation-induced interfacial strain mismatch, to fabricate auto-detachable, freestanding, and patternable electrodes. The SHAPE method utilizes vacuum-filtration of polyaniline/bacterial cellulose (PANI/BC) ink through a masked filtration membrane to print high-resolution, patterned, and multilayer electrodes. The strong interlayer hydrogen bonding ensures robust multilayer integrity, while the controllable evaporative shrinking property of PANI/BC induces mismatch between the strains of the electrode and filtration membrane at the interface and thus autodetachment of electrodes. Notably, a 500-layer substrateless micro-supercapacitor fabricated using the SHAPE method exhibits an energy density of 350 mWh cm-2 at a power density of 40 mW cm-2 , 100 times higher than reported substrate-confined counterparts. Moreover, a digital circuit fabricated using the SHAPE method functions stably on a deformed glove, highlighting the broad wearable applications of the SHAPE method.